ANALISIS TEKNIKAL SAHAM MENGGUNAKAN VARIABLE INDEX DYNAMIC AVERAGE (VIDYA) - , ROSELINA YOLANDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Our financial and market action change every minute of every day. These markets are dynamic because traders constantly adjust to changing perceptions and participants. Therefore we need dynamic indicators that vary the time periode used in analyzing market action. Variable Index Dynamic Average (VIDYA) is an indicator that adapted Exponential Moving Average (EMA) that can dynamically follow the movements of stock prices. Equal as Exponential Moving Average (EMA), VIDYA also need weight in its calculation methods. In this paper, the weight of EMA is used to determine the weight of VIDYA. VIDYA can be calculated using three different methods, such as standard deviation, Chande Momentum Oscillator (CMO), and coefficient of determination. These calculation method is used to determine the volatility index that worth to predict stock price movements and predict the trend in the future. In addition, VIDYA can be used as trading strategy and determine buy signal or sell signal that using the breakout point. Keyword: technical analysis, volatility index, exponential moving average, standard deviation, coeffitient of determination, momentum indicator